Digital Calibration Certificates (DCC): Benefits and Challenges to overcome for implementation - Koval Martin; Tesař Jiří; Schönhals Shanna; Sharma Anjali; Balslev-Harder David; Galvan-Hernandez Carlos; Baumann Henri; Mahovský David (EPJ Web of Conferences)
The term Digital Calibration Certificate (DCC) has been increasingly prevalent in the metrology field, with national and international conferences where stakeholders discuss DCC. This article delves into the implications of integrating “D - digitalization” into “CC - calibration certificate,” exploring the significant impact this concept brings to well-established practices. DCC represents a logical progression in the digitalization of metrology. Despite the existence of initial DCC implementations, it is essential to highlight the challenges that must be addressed before full-scale deployment. The discussion in the article focuses on raising questions about what DCC represents and the critical areas of focus before full deployment. The transition from paper-based calibration certificates to digital ones involves significant changes in the mindset of society to increase trustworthy in digital technologies. DCCs promise numerous benefits, including enhanced efficiency, traceability, and reliability in calibration processes, aligning with the broader trend of digital transformation in various industries. However, achieving these benefits requires a thorough understanding of the associated challenges. This article examines the aspects of DCCs, aiming to provide an overview of their benefits and the hurdles to be overcome for widespread acceptance.